Laboratory vs. in situ resin‐core methods to estimate net nitrogen mineralization for comparison of rotation and tillage practices. Issue 3 (24th April 2017) - Zou, Congming; Pearce, Robert C.; Grove, John H.; Coyne, Mark S.
Abstract: Properly estimating soil nitrogen (N) mineralization as a consequence of different agronomic practices would result in better soil N fertility management. In this study, we tested the differences between laboratory and in situ resin‐core incubation methods for estimating soil net N mineralization for long‐term burley tobacco ( Nicotiana tobacum L .) tillage and rotation systems. The laboratory incubation method used crushed, homogenized, litter‐free soil samples, and the in situ resin‐core incubation method used an intact soil core with the inclusion of any plant residue below or above ground. Comparisons showed that no‐tillage had significantly increased soil net N mineralization compared to conventional tillage with the laboratory incubation method, while there was no significant difference between tillage methods with the in situ resin‐core method. This indicates that soil pretreatment in the laboratory incubation method can create an "artificial tillage effect" for soil previously managed with no‐tillage, resulting in overestimated soil net N mineralization. The rotation comparison showed that different crop sequences had no impact on measured net N mineralization with the laboratory incubation method. However, a preceding soybean crop did significantly increase net soil N mineralization compared to preceding corn when measured with the in situ resin‐core method. This suggests that discarding plant residue in the laboratory incubation method can neglect the potential effect of plant residue on soil N mineralization. Therefore, it is important to be aware that soil pretreatment may influence soil N mineralization estimates, potentially resulting in flawed decisions for soil N fertility management.